Relevansi Hybrid Learning Method pada Mata Kuliah Ilmu Ma’ani Bagi Mahasiswa Mobility di Unisza - Dina Wilda Sholikha; Eko Asmanto (Jurnal Ragam Pengabdian, 2025)
Digital transformation in education has encouraged the emergence of hybrid learning models that combine face-to-face and online sessions to enhance learning flexibility and quality. In the context of the student exchange program between Universitas Muhammadiyah Sidoarjo and Universiti Sultan Zainal Abidin, hybrid learning is applied to the Ilmu Ma’ani course, which requires a deep understanding of classical Arabic texts. This study aims to analyze the relevance of hybrid learning to students’ comprehension of Ilmu Ma’ani and to explore their cross-cultural learning experiences within the exchange program. The research employs a descriptive qualitative approach, with data collected through in-depth interviews involving exchange students and the course instructor. The data were analyzed using thematic analysis to identify patterns of experiences, challenges, and perceptions expressed by the informants. The findings indicate that hybrid learning offers advantages in improving access to learning resources, opening opportunities for international collaboration, and facilitating flexible learning. However, face-to-face instruction remains more effective, particularly for concept-based courses such as Ilmu Ma’ani, because direct interaction is considered more helpful for understanding the context of classical Arabic texts. Technical challenges, such as internet connectivity issues and limitations in online communication, also affect student participation. This study concludes that hybrid learning is relevant as a supportive method but should not serve as the primary learning approach in the Ilmu Ma’ani course. The findings provide recommendations for optimizing the implementation of hybrid learning in future Islamic studies–based student exchange programs.